Tribological Characteristics of the Magnesium Matrix-Glassy Carbon Particles Composite Manufactured by Different Casting Methods. (5th May 2015) - Olszówka-Myalska, Anita; Myalski, Jerzy; Hekner, Bartosz
Abstract : A particulate composite with a magnesium matrix (Mg3Al) and glassy carbon particles (GCp) obtained under industrial conditions from a gravity cast and pressure die cast suspension was examined. The influence of the casting procedure on the microstructure and mechanical properties was revealed. Sliding friction tests by the pin-on-disc method for different loads (2.3, 5, and 9.3 N) and speeds (0.06, 0.09, and 0.14 m/s) were performed. Regardless of the technology, the sliding friction coefficient's value strongly depended on the load and speed. Its value was changing (0.35–0.13) and was usually higher for the pressure die cast material, yet the wear resistance of the composite processed in that way was considerably better compared with the gravity cast. The results of the worn surface observation by SEM with EDS showed an influence of the initial Mg3Al-GCp composite's microstructure on the processes of its wear.